Who are the value and growth investors? - Sebastien Betermier; Laurent E. Calvet; Paolo Sodini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
This paper investigates the determinants of value and growth investing in a large administrative panel of Swedish residents over the 1999-2007 period. We document strong relationships between a household's portfolio tilt and the household's financial and demographic characteristics. Value investors have higher financial and real estate wealth, lower leverage, lower income risk, lower human capital, and are more likely to be female than the average growth investor. Households actively migrate to value stocks over the life-cycle and, at higher frequencies, dynamically offset the passive variations in the value tilt induced by market movements. We verify that these results are not driven by cohort effects, financial sophistication, biases toward popular or professionally close stocks, or unobserved heterogeneity in preferences. We relate these household-level results to some of the leading explanations of the value premium.
Keywords: G11; G12; 330; asset pricing; value premium; household finance; portfolio allocation; human capital; G-SIFIs